2019
DOI: 10.1051/meca/2020056
|View full text |Cite
|
Sign up to set email alerts
|

Proof of a composite repair concept for aeronautical structures: a simplified method

Abstract: This paper provides an illustration of all stages of primary aeronautical composite structure repair by using industrial tools and scientific methodologies, as well as numerical tools to simplify the cross-over analysis of the mechanical behaviour of the repaired area. Economically and scientifically speaking, one of the main challenges of composite repair (for monolithic long fiber composite parts) consists of promoting a bonded composite patch option without additional riveted doublers. To address this chall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…A novel machining technique has been developed to perform in-situ stepped repairs. It uses water-jet abrasion instead of traditional hand abrasion, making the machining process faster and more reliable [16,17]. In terms of equivalent scarf angle based on the ratio between total repair thickness and length, tested configurations go from 5.2° to 1.3° angles.…”
Section: Problem Definitionmentioning
confidence: 99%
“…A novel machining technique has been developed to perform in-situ stepped repairs. It uses water-jet abrasion instead of traditional hand abrasion, making the machining process faster and more reliable [16,17]. In terms of equivalent scarf angle based on the ratio between total repair thickness and length, tested configurations go from 5.2° to 1.3° angles.…”
Section: Problem Definitionmentioning
confidence: 99%
“…It was observed that as the number of steps increased, the strength of the repair increased. Collombet et al [46] presented results showing stepped joints with a specific layup only made of +-±45° plies failing by laminate fracture with no debonding at all. They concluded that the stepped joint was not always the weakest part of the assembly.…”
Section: Specimens Typologymentioning
confidence: 99%
“…Further experimental and numerical work, including damage modelling simulations, is needed to provide an understanding of the differences between failure behaviour of a flush repair and its equivalent joint, and to what extent the equivalent joints hypothesis is valid. This could help saving computation time in strength prediction simulations because even for small coupons, detailed FE models can reach more than 500.000 degrees of freedom [46].…”
Section: Representativeness Of the Equivalent Jointmentioning
confidence: 99%
See 1 more Smart Citation